2004
DOI: 10.1111/j.1395-3907.2004.00290.x
|View full text |Cite
|
Sign up to set email alerts
|

Ocular refractive changes in patients receiving hyperbaric oxygen administered by oronasal mask or hood

Abstract: ABSTRACT.Purpose: The aim of this study was to quantify ocular refractive changes after a standard hyperbaric oxygen (HBO) treatment protocol and to characterize the time period of recovery. Patients and Methods: Hyperbaric oxygen therapy was given for 90 min daily at a pressure of 240 kPa for 21 days. Oxygen was administered to 20 patients using an oronasal mask and to 12 patients using a hood. Follow-up examinations were carried out 2-4 days after treatment, and thereafter regularly for up to 10 weeks in bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
1
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 20 publications
2
30
1
1
Order By: Relevance
“…The most undesirable side effect of HBO therapy is oxygen toxicity caused by the use of high levels of oxygen. Reversible myopia forms with toxic effects on the lens and resolves within weeks after the completion of treatment [21]. Central nervous system oxygen toxicity and epileptic episodes may be observed, but these do not cause permanent damage.…”
Section: Principles Of Hyperbaric Oxygen Therapymentioning
confidence: 95%
“…The most undesirable side effect of HBO therapy is oxygen toxicity caused by the use of high levels of oxygen. Reversible myopia forms with toxic effects on the lens and resolves within weeks after the completion of treatment [21]. Central nervous system oxygen toxicity and epileptic episodes may be observed, but these do not cause permanent damage.…”
Section: Principles Of Hyperbaric Oxygen Therapymentioning
confidence: 95%
“…Although extensive clinical studies are still lacking, adjunctive HBO therapy is suggested in the treatment of some ophthalmologic disorders such as central retinal artery occlusion, anterior segment ischemia, corneal edema, and diabetic macular edema [5] . Ophthalmologic complications such as myopic shift and nuclear cataract formation may develop in patients receiving HBO treatment [6][7][8][9] .…”
Section: Introductionmentioning
confidence: 99%
“…The intermittent inhalation of oxygen with air breaks and use of 2.0 ATA reduces the incidence of oxygen toxicity. Reversible myopia arises due to toxic effects on the lens and resolves within weeks after the completion of treatment [67]. The symptoms of CNS oxygen toxicity include twitching, auditory hallucinations, disorientation and seizures.…”
Section: Treatment Protocolmentioning
confidence: 99%